A Bipolar Fermatean Fuzzy Hamacher Approach to Group Decision-Making for Electric Waste (European Journal of Pure and Applied Mathematics, 2025)
The paper introduces advanced aggregation operators based on Hamacher operational laws for Bipolar Fermatean Fuzzy sets, addressing complex decision-making problems. In addition, a score function is utilized to evaluate and rank alternatives within the Bipolar Fermatean Fuzzy decision framework, offering a quantitative measure of each alternative’s performance based onthe aggregation results. This score function helps simplify decision-making, particularly in cases involving complex uncertainty and multiple criteria. The proposed operators include the Bipolar Fermatean Fuzzy-Hamacher weighted average, the Bipolar Fermatean Fuzzy-Hamacher Ordered Weighted Average, and the Bipolar Fermatean Fuzzy-Hamacher Hybrid Weighted Average. These operators are designed to integrate membership, nonmembership, and hesitation degrees, making them highly effective in Bipolar Fermatean Fuzzy environments. To demonstrate the practicality of the proposed approach, a real-world group decision-making scenario is applied to managing electronic waste. The results show the proposed methodology’s superior efficiency, flexibility, and precision compared to existing approaches. The findings highlight the robustness of operators in handling uncertainty and enhancing the accuracy of decision-making.
Keywords: bipolar valued fuzzy binary operation